Story Telling Competition at Langsep Challenge 2022 At Santa Maria Langsep Catholic High School, Malang - Andy Endra Krisna; Rini Susrijani (ARDHI : Jurnal Pengabdian Dalam Negri, 2023)
The storytelling competition, as one of the featured competitions in the 2022 Langsep Challenge at Santa Maria Langsep Catholic High School, Malang, was the main highlight of the event. This event showcases the creativity and expertise of the competition participants in telling stories in an interesting and engaging way. Participants from various junior high schools compete to win the champion title in this competition. The various stories presented include interesting themes related to folklore. The competition jury, which consists of experienced lecturers, observes and assesses each participant's presentation based on criteria such as grammar, vocabulary, pronunciation, how to tell a story, mastery of the stage, clothing, properties used, moral message, time management, and so on. This competition is not only an opportunity to show students' speaking skills, but also develop creative thinking and self-expression skills. With full support from the school and the enthusiasm of the participants, the Story Telling Competition at Langsep Challenge 2022 created an atmosphere full of enthusiasm and joy among students.